Centering Equity in Community College Virtual International Exchange: An Exploration of Program Typology and Participant Demographics - Whatley, Melissa; LaVenture, Suzanne; Russell, Nadine (Journal of International Students, 2022)
Using data from two community colleges in the US southeast, this study uses an equity-focused research lens to address two complementary purposes. First, it situates community college virtual exchange programs within a pre-existing program typology to explore how well these programs are represented. Second, it examines demographic characteristics of community college students who participate in virtual exchange and compares them to students who study abroad to provide insight into the extent to which community college virtual exchange programs improve access to international education. Results indicate that while community college virtual exchange programs often fit well within the typology, broad, open-access exchanges were not as well-described, nor were programs that were not explicitly connected to a cost. Regarding access, findings suggested that some demographic groups, particularly Black students, were less likely to access virtual exchange. Institutional structures related to a student’s degree program offer a potential explanation for this finding.